Integrated single-cell and transcriptomic analysis of bone marrow-derived metastatic neuroblastoma reveals molecular mechanisms of metabolic reprogramming - Jing Chu; Rong Qin; Shu-Jing Wang; Qiang Wang; Qiang Wu (Scientific Reports)
Abstract Neuroblastoma (NB) is the most common extracranial solid tumor in early childhood and frequently presents with bone marrow (BM) metastasis, particularly in high-risk cases. Metastatic NB cells residing in the BM exhibit distinct biological behaviors and are closely associated with treatment resistance and poor prognosis. Emerging evidence suggests that metabolic reprogramming is a hallmark of NB progression; however, its regulatory landscape within the bone marrow microenvironment remains poorly understood. This study aimed to systematically elucidate the molecular mechanisms underlying metabolic reprogramming in bone marrow–infiltrating metastatic NB cells by integrating single-cell transcriptomic data, bulk RNA-sequencing profiles, and in vitro functional validation. Single-cell RNA-sequencing data from 17 bone marrow aspirates of NB patients—with and without marrow infiltration—were retrieved from the GEO database, while bulk RNA-seq data from 155 NB tumor samples were obtained from the TARGET database. A suite of bioinformatics tools, including Seurat, Harmony, CellChat, and SCENIC, was employed to perform multi-dimensional analyses such as cell subtype annotation, intercellular communication mapping, and transcription factor regulon construction. AUCell scoring, differential gene expression analysis, random survival forest modeling, and Kaplan–Meier survival analysis were conducted to identify key genes involved in metabolic reprogramming and to characterize their immune infiltration features. Gene Set Enrichment Analysis (GSEA), Gene Set Variation Analysis (GSVA), and single-cell pathway scoring were applied to predict the metabolic and immune pathways associated with these candidate genes. Furthermore, co-expression network analysis was used to evaluate the relationships between candidate genes and known NB regulatory factors. Finally, in vitro experiments were carried out to validate the roles of selected genes in regulating NB cell proliferation, migration, invasion, and mitochondrial function. Single-cell transcriptomic analysis of bone marrow–derived NB samples identified nine distinct cell subpopulations with diverse intercellular communication networks. Among these, the ligand–receptor pair MDK–NCL emerged as a key mediator of cell–cell signaling. Regulatory network analysis revealed five critical regulons—JUND, JUNB, FOS, E2F1, and KLF16—closely associated with metabolic reprogramming in NB. The “Neuroblastoma cell” cluster displayed markedly elevated metabolic activity. Through integrated analyses, five core metabolic reprogramming genes (MRPL21, NHP2, RPL13, RPL18A, and RPL27A) were identified and shown to be significantly associated with poor prognosis. High expression of these genes correlated with an immunosuppressive tumor microenvironment, characterized by reduced infiltration of monocytes, M1 macrophages, and T cells. Functional enrichment analysis revealed that these genes were primarily enriched in oxidative phosphorylation, MYC targets, PI3K-Akt, and p53 signaling pathways. Co-expression network analysis further demonstrated that MRPL21 and NHP2 positively correlated with known NB regulatory genes TP53, NRAS, and NKIF1B. In vitro assays confirmed that MRPL21 knockdown significantly impaired NB cell proliferation, migration, invasion, and mitochondrial oxidative phosphorylation. This study identified five key genes involved in metabolic reprogramming of bone marrow–infiltrating NB cells, which are closely associated with immunosuppressive microenvironment formation and enrichment in tumor-associated metabolic pathways. Among these, MRPL21 plays a pivotal role in regulating NB cell proliferation and mitochondrial function, underscoring its potential as a promising therapeutic target. These findings suggest that integrated strategies targeting both tumor metabolism and the immune microenvironment may provide new avenues for the treatment of high-risk, metastatic NB.